Pengaruh Latihan Passing Squence (Look For Position) dan Latihan Passing Squence (Speed Dribbling) Terhadap Kemampuan Passing Pemain Sepak Bola PS. Mujur Tahun 2023 - Maulidi, Muh. Zainul; Yusuf, Muhammad; Zainuddin, Fadli (JUPE : Jurnal Pendidikan Mandala, 2023)
: "The Effect of Passing Sequence Training (Look For Position) and Passing Sequence Training (Speed Dribbling) on the Passing Ability of PS Football Players. Mujur Tahun 2023".PS Mujur is one of the football clubs located in Mujur Village, East Praya District, Central Lombok Regency, West Nusa Tenggara Province, which is one of the many football clubs that actively trains and regularly participates in various tournaments. From the author's previous observations, there are still many problems that must be addressed in the club, one of which attracts the author's attention is the passing ability which still has many passing errors in training and matches. Passing Sequence (Look For Position) training and Passing Sequence (Speed Dribbling) training which aims to improve passing ability. The purpose of the study was to determine the effect of Passing Sequence Training (Look For Position) and Passing Sequence Training (Speed Dribbling) on the Passing Ability of PS Football Players. Mujur Year 2023. The instrument in this study was a passing ability test. From the results of statistical data analysis The count value of X1 football passing test on Passing Sequence (Look For Position) training is 7.2 the value simultaneously between Y and X concludes table analysis at a significant level of 5% with the number of samples (n - 1) which is 9 amounting to 1.833 So it can be concluded that seen from the tcount> table ¬¬ 7.2> 1. 833 and From the results of statistical data analysis X2 thing value of football Shooting test on Passing Sequence Exercise (Speed Dribbling) amounting to 6.7 simultaneous value between Y and X draw conclusions table analysis at a significant level of 5% with the number of samples (n - 1) ie 9 amounting to 1.833 So it can be concluded that judging from t count > t tabel ¬¬ 6.7 > 1.833).